The Possibilities of Using the Audit of the Quality Management System to Improve the Efficiency of Public Administration - Čandrlić - Dankoš, Ivana (Oeconomica Jadertina, 2017)
According to the international requirements of ISO 9001:2015, the conducting of the audit of the quality control system is a key prerequisite for checking the compliance of the system with the international standards requirements and the requirements of the organization's quality management system that applies them. The results of conducted internal audits contain information related to irregularities (noncompliance with the required norms), and recommendations for improvement, all of it aimed towards improving the existing business practices. Simultaneously, the analysis of the position of the Republic of Croatia on international competitiveness charts shows a significant lag in relation to the countries of Central and Eastern Europe. The analysis of the comparison of the Republic of Croatia with other countries based on the analysis of international competitiveness shows lagging in all segments of competitiveness. Consequently, in line with the recommendations of the European Commission as part of the convergence program of national reforms in the Republic of Croatia, the weakness of the system is also reflected in the (non) efficiency of the public sector that needs to be improved. The work of local and regional self-government units (hereinafter referred to as management) in the Republic of Croatia is supervised by State administration bodies, institutions responsible for conducting business of legal and/or natural persons, assemblies in towns and counties, and within municipalities the municipal council as well as internal audit units and internal auditors if the management has implemented a quality management system according to one of the international standards. The question arises about the possibility of using audits as a form of quality management control as a strategic tool for improving the work of the administration, or more precisely the increasing of the efficiency of the system and raising the level of competitiveness. This paper gives a brief overview of the efficiency of the Croatian public administration presented through international competitiveness charts, an overview of the forms of work management oversight, with special emphasis on monitoring specificities according to the international standard ISO 9001:2015 and the Quality Control and Auditing Guidelines standard methodology and the ISO / IEC 19011: 2012. Professional and scientific literature regarding the experiences and the role of internal auditing in public administration has been consulted. The concluding remarks analyze the possibilities of using internal audits as the basis for improving the quality of the management system.
Keywords: internal audit; public sector; management efficiency; strategic tool; ISO 9001; 2015